Bacillus cereus (EG-Q3) in the Gut of Ectropis grisescens Contributes to Host Response to Starvation Conditions - Li, Xiayu; Zhang, Yong; Zhou, Linlin; Gao, Tian; Zhao, Yu; Liu, Song; Su, Qingqing; Wei, Chaoling; Yang, Yunqiu; Long, Yanhua (Frontiers in Microbiology, 2022)
The gut bacteria of insects plays an important role in their nutrition, maintenance, and ecological adaption. Ectropis grisescens is the most important leaf-feeding pest of tea gardens in China. In order to explore whether the adaptation of E. grisescens under starvation stress is related to its gut bacteria, we used a culture-independent method to compare the composition and diversity of gut bacteria under starvation treatment. The results revealed no significant changes in core gut bacteria composition and diversity within 24 hours of starvation. However, non-core gut bacterial Bacillus was significantly increased under starvation conditions. B. cereus strain EG-Q3 isolated from the gut of E. grisescens in carbon source-selected medium showed the ability to degrade fat bodies from E. grisescens in vitro and in vivo. Moreover, the fat-lowering ratio of E. grisescens fed with B. cereus strain EG-Q3 (6.76 ± 1.281%) was significantly higher than that of control group (3.96 ± 0.801%, t = 4.15, df = 8, p < 0.01) after starvation for 4 h. These findings suggest that non-core gut bacterial B. cereus strain EG-Q3 contributes to host adaptation to starvation. Together, this research provides evidence that E. grisescens may benefit from non-core gut bacteria under starvation conditions.